2021
DOI: 10.1101/2021.05.13.444014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Serotonergic Neurons Translate Taste Detection into Internal Nutrient Regulation

Abstract: The nervous and endocrine systems coordinately monitor and regulate nutrient availability to maintain energy homeostasis. Sensory detection of food regulates internal nutrient availability in a manner that anticipates food intake, but sensory pathways that promote anticipatory physiological changes remain unclear. Here, we identify serotonergic (5-HT) neurons as critical mediators that transform gustatory detection by sensory neurons into the activation of insulin-producing cells and enteric neurons in Drosoph… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Previous studies demonstrated that the serotonergic neurons in the lateral side of the gnathal ganglion facilitated the food ingestion of D. melanogaster larvae ( Schoofs et al, 2018 ). In addition to the internal regulation, the serotonergic neurons of the gnathal ganglion were also involved in mediating taste detection ( Yao and Scott, 2021 ). One class of serotonergic neurons in the gnathal ganglion responds to gustatory detection of sugars and the other class to gustatory detection of bitter compounds ( Yao and Scott, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that the serotonergic neurons in the lateral side of the gnathal ganglion facilitated the food ingestion of D. melanogaster larvae ( Schoofs et al, 2018 ). In addition to the internal regulation, the serotonergic neurons of the gnathal ganglion were also involved in mediating taste detection ( Yao and Scott, 2021 ). One class of serotonergic neurons in the gnathal ganglion responds to gustatory detection of sugars and the other class to gustatory detection of bitter compounds ( Yao and Scott, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the internal regulation, the serotonergic neurons of the gnathal ganglion were also involved in mediating taste detection ( Yao and Scott, 2021 ). One class of serotonergic neurons in the gnathal ganglion responds to gustatory detection of sugars and the other class to gustatory detection of bitter compounds ( Yao and Scott, 2021 ). As in other species, larval S. frugiperda possesses taste sensilla on the maxilla, responding to the stimuli sugar and bitter substances to regulate the feeding preference ( Hou et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analysis was carried out in Python using the SciPy package, version 1.7.3 (https://www.nature.com/articles/s41592-019-0686-2). deltaF/F0 images were created as described 40 .…”
Section: Methodsmentioning
confidence: 99%
“…Statistical analysis was carried out in Python using the SciPy package, version 1.7.3 (https://www.nature.com/articles/s41592-019-0686-2). deltaF/F0 images were created as described 38 . In vivo functional connectivity experiments: In vivo sample preparation for calcium imaging was performed as described 29 .…”
Section: Methodsmentioning
confidence: 99%
“…TCA were performed similarly to those reported by Yao and Scott (2022). Two-four days old mated females were food-deprived for 22 hours and prepared for experiments as above (Fig.…”
Section: Behavioral Assaysmentioning
confidence: 99%